The pro and anti-inflammatory activities of immunoglobulin G - Lux, Anja; Aschermann, Sarah; Biburger, Markus; Nimmerjahn, Falk (Annals of the Rheumatic Diseases, 2010)
Immunoglobulin G (IgG) molecules are a family of glycoproteins essential for defending the body against invading pathogens. The antibody constant domain is very potent in initiating proinflammatory pathways such as the activation of innate immune effector cells via cellular receptors specific for the antibody constant region (Fc receptors) and the activation of the complement pathway. During autoimmune disease the normally protective antimicrobial function of these molecules is targeted to healthy tissues often with disastrous consequences. Interestingly, one successful anti-inflammatory therapy for many autoimmune diseases is the infusion of high doses of IgG molecules, the so-called intravenous IgG therapy. How one class of molecules can have such opposing functions will be the major focus of this review.